Studi Awal Solar Water DistillerAir Laut Dengan Limbah Botol Plastik Untuk Penyediaan Air Bersih: Endarko, Suasmoro, Triwikantoro, Agus Purwanto, Zaenal Arifin, Mashuri, Yoyok Cahyono, Yanurita Dwi Hapsari, Heru Sukamto, Suminar Pratapa, Herliansyah, Fachrina Maryam, Mira Anjani, dan Niken Rancangkapti - Endarko Endarko; Suasmoro Suasmoro; Triwikantoro Triwikantoro; Agus Purwanto Agus Purwanto; Zaenal Arifin Zaenal Arifin; Mashuri Mashuri; Yoyok Cahyono Yoyok Cahyono; Yanurita Dwihapsari Yanurita Dwihapsari; Heru Sukamto Heru Sukamto; Suminar Pratapa Suminar Pratapa; Herliansyah Herliansyah; Fachrina Maryam Fachrina Maryam; Mira Anjani Mira Anjani; Niken Rancangkapti Niken Rancangkapti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2018)
It has been successfully investigated the utilization of waste plastic bottles as a solar water distiller for the provision of clean water. In this study 600 and 1500 mL plastic bottles used for solar water distiller with 9 variations. A 600 mL bottle with a variation of the addition of soda cans painted black or not (3 variations) as type A. Hereinafter, 600 mL plastic bottle connected with 1500 mL plastic bottle positioned above 600 mL bottle contained small plastic bottle placed in bottle 1500 mL with variations of either painted black or not (3 variations) is called type B. Moreover, the next three variations are 1500 mL bottles cut in half to resemble open containers with smaller plastic bottles placed inside whether painted black or not (Type C). Furthermore, as a comparison of plastic containers (basin) with a diameter of 25 cm used for the solar distiller. The study was conducted with 30 mL of seawater as the initial data, after 8 hours exposed to the sunlight. The results showed that plastic containers had better efficiency compared to all types of the plastic bottle as solar distiller with the value up to (55.7 ± 3.1)%, while for the distillation system with plastic bottles, the highest efficiency was obtained type distillation system A with a range of 11-13%. While for type B and C respectively equal to 1-4%.